2011
DOI: 10.1103/physrevb.83.059902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Phase transitions and phase diagram of the ferroelectric perovskite (Na0.5Bi0.5)et al.

Abstract: In the legend in the upper right-hand corner of Fig. 9, the label T 3 for the dielectric measurements (downward pointing triangle) should be replaced with T 2 . The rest of the paper is unaffected by this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…Here, the {110} and {111} peaks are observed to narrow with increasing temperature (Figure 1a) with both peaks reach a minimum width in the range 300-320 °C, clearly indicating that this is a phase transition, in agreement with other studies. [5][6][7] Whilst the equivalent peak widths from solid-state NBT also show this phase transition (Figure 1b), the overall change in peak widths is significantly smaller than for hydrothermal NBT, which therefore evidences this particular transition much more clearly than has been seen before. The increase in the {110} peak width above this phase transition is consistent with emerging tetragonal symmetry, indicating 300 (10) °C as the pseudo-rhombohedral-tetragonal phase transition temperature, in agreement with optical birefringence measurements.…”
Section: Textmentioning
confidence: 70%
See 1 more Smart Citation
“…Here, the {110} and {111} peaks are observed to narrow with increasing temperature (Figure 1a) with both peaks reach a minimum width in the range 300-320 °C, clearly indicating that this is a phase transition, in agreement with other studies. [5][6][7] Whilst the equivalent peak widths from solid-state NBT also show this phase transition (Figure 1b), the overall change in peak widths is significantly smaller than for hydrothermal NBT, which therefore evidences this particular transition much more clearly than has been seen before. The increase in the {110} peak width above this phase transition is consistent with emerging tetragonal symmetry, indicating 300 (10) °C as the pseudo-rhombohedral-tetragonal phase transition temperature, in agreement with optical birefringence measurements.…”
Section: Textmentioning
confidence: 70%
“…4 However, the deviation from rhombohedral symmetry is very small and the room-temperature structure may be considered pseudo-rhombohedral. On heating, a phase transition to tetragonal symmetry is known to exist, but has been reported to take place over a range of temperatures: 278-291 °C, 5 240-270 °C 6 and 300-320 °C. 7 At the boundary between pseudorhombohedral and tetragonal structures, some studies 8 have shown the existence of a two-phase region, while others 9 have proposed the presence of an intermediate phase.…”
Section: Textmentioning
confidence: 99%
“…For BNT-based piezoceramics, T c is also frequently reported in the literature; although, because of the relaxor behavior of these materials, the temperature of maximum permittivity T m cannot be considered a Curie point. 10,11 Moreover, the degradation of piezoelectric properties often takes place around an additional transition temperature referred to as depolarization temperature T d , which is found well below T m . In BNT-based systems, there is a weakly polar intermediate phase, 12 which occurs between the T d and T m .…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, recent investigations of Na 1/2 Bi 1/2 TiO 3 -xat.%BaTiO 3 (NBT-x%BT) have revealed giant strain and longitudinal piezoelectric constants as high as d 33 ¼ 500 pC/N for compositions near a morphotropic phase boundary (MPB) around x ¼ 5.5-6.5. [3][4][5][6][7][8][9][10][11][12][13] In spite of a non-rhombohedral average structure model for NBT at room temperature was supported by highresolution single-crystal x ray diffraction, 14 it is still widely accepted that NBT undergoes a phase transformational sequence of paraelectric cubic (C) ! paraelectric tetragonal (T) !…”
mentioning
confidence: 99%
“…22 Support of these observations has also been reported by anelastic measurements. 6 High resolution transmission electron microscopy (HRTEM) has shown that the lattice is partially incoherent across the boundaries between polar nano-regions. 25 Formation of planar defects along the domain boundaries may help relax the elastic energy in this geometrically frustrated condition.…”
mentioning
confidence: 99%